Generation of novel Il2rg-knockout mice with clustered regularly interspaced short palindromic repeats (CRISPR) and Cas9 - Byambaa, Suvd; Uosaki, Hideki; Hara, Hiromasa; Nagao, Yasumitsu; Abe, Tomoyuki; Shibata, Hiroaki; Nureki, Osamu; Ohmori, Tsukasa; Hanazono, Yutaka (Experimental Animals, 2020)
X-linked severe combined immunodeficiency (X-SCID) is an inherited genetic disorder. A majority of X-SCID subjects carries point mutations in the Interleukin-2 receptor gamma chain (IL2RG) gene. In contrast, Il2rg-knockout mice recapitulating X-SCID phenotype lack a large part of Il2rg instead of point mutations. In this study, we generated novel X-SCID mouse strains with small insertion and deletion (InDel) mutations in Il2rg by using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9. To this end, we injected Streptococcus pyogenes Cas9 (SpCas9) mRNA and single guide RNA targeting the exon 2, 3 or 4 of Il2rg into mouse zygotes. In the F0 generation, we obtained 35 pups and 25 out of them were positive for Surveyor assay, and most of mutants displayed dramatic reductions of T and B lymphocytes in the peripheral blood. By amplicon sequencing, 15 out of 31 founder mice were determined as monoallelic mutants with possible minor mosaicisms while 10 mice were mosaic. Finally, we established new strains with 7-nucleotide deletion and 1-nucleotide insertions in the exon 2 and the exons 3 and 4, respectively. Although no IL2RG protein was detected on T cells of exons 3 and 4 mutants, IL2RG protein was unexpectedly detected in the exon 2 mutants. These data indicated that CRISPR/Cas9 targeting Il2rg causes InDel mutations effectively and generates genetically X-SCID mice. Genetic mutations, however, did not necessarily grant phenotypical alteration, which requires an intensive analysis after establishing a strain to confirm their phenotypes.